Documenta Information 2. - Helms, Dietrich (Kassel : Museum Fridericianum, 1968)
Segal ; Jaquet, Alain ; Paolozzi, Eduardo ; Oldenburg, Claes ; Lenk, Thomas ; Fruhtrunk ; Rauschenberg, Robert ; Lichtenstein, Roy ; etc.
Internationale Ausstellung 4. Documenta Kassel '68, 27. Juni bis 6. Oktober 1968
boek